1988
DOI: 10.1111/j.1558-5646.1988.tb02493.x
|View full text |Cite
|
Sign up to set email alerts
|

HERITABILITY AND SELECTION ON CLUTCH SIZE IN DARWIN'S MEDIUM GROUND FINCHES (GEOSPIZA FORTIS )

Abstract: Abstract.-I studied the causes ofvariation and selection on clutch size in a population ofDarwin's Medium Ground Finches (Geospizafortis) on Isla Daphne Major, using data collected over a nineyear period (1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984). Quantitative-genetic analyses were carried out using the first clutch laid by a female in a given year. I used both unadjusted clutch-size values and values adjusted for between-year differences in mean clutch size for repeatability and regression analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Apart from the technical aspect of violating the assumption of reaction norm linearity more seriously when the among-year component of V P is greater, there is also the biological aspect that there may exist stronger selection for plasticity in fluctuating and unpredictable environments. Across the (limited number of) studies in Table 1, there is, however, no evidence for a negative correlation between heritability and the amount of between-year phenotypic variance (including Gibbs (1988), Pearson r ϭ Ϫ0.60, P ϭ 0.16; excluding Gibbs (1988), Pearson r ϭ 0.34, P ϭ 0.50).…”
Section: Variation Among Yearsmentioning
confidence: 98%
See 4 more Smart Citations
“…Apart from the technical aspect of violating the assumption of reaction norm linearity more seriously when the among-year component of V P is greater, there is also the biological aspect that there may exist stronger selection for plasticity in fluctuating and unpredictable environments. Across the (limited number of) studies in Table 1, there is, however, no evidence for a negative correlation between heritability and the amount of between-year phenotypic variance (including Gibbs (1988), Pearson r ϭ Ϫ0.60, P ϭ 0.16; excluding Gibbs (1988), Pearson r ϭ 0.34, P ϭ 0.50).…”
Section: Variation Among Yearsmentioning
confidence: 98%
“…Of the 11 studies that had sufficient statistical power, 10 found significant heritabilities for clutch size, ranging from 0.21 to 0.48. Only Gibbs (1988) found very small, nonsignificant repeatabilities and heritabilities for first clutch sizes in Darwin's Medium Ground Finches (Geospiza fortis). Except for Van Noordwijk et al (1981), Lessells et al (1989), and the more recent studies mentioned, all of these studies use fewer than 10 years of data.…”
Section: Heritability Estimatesmentioning
confidence: 99%
See 3 more Smart Citations